Frequency Dependent Attenuation Characteristics of Body Waves in Büyük Menderes Graben - Alper Demirci; Tolga Bekler (Doğal Afetler ve Çevre Dergisi)
In this study, 66 earthquake data, along the faults of northern boundary of the Büyük Menderes Graben and their continuations in the Aegean Sea, were used to reveal the body wave attenuation characterization of the region. The attenuation functions of the P and S waves are calculated by the coda normalization technique. The results obtained in this study reveal attenuation relations, which are one of the basic parameters required to modelling large earthquakes in the region and to obtain more reliable results from necessary seismic risk studies. The power-law functions were obtained for the S and P seismic phases as Qs=79.2±14.6f 0.9±0.07 and Qp=32.9±13.7f1.05±0.16 respectively. Also the QS / QP ratio is calculated as ~ 1.75. for the frequencies greater than 1 Hz. According to the results, the low Qp and Qs values ​​and their ratios (QS / QP) indicate the abundance of scattering effect, which can be interpreted as a result of intense lateral heterogeneity in the upper crust.